1980
DOI: 10.3109/03009738009179185
|View full text |Cite
|
Sign up to set email alerts
|

Local Inhibition of the Fibrinolytic System in Patients with Massive upper Gastrointestinal Hemorrhage

Abstract: The effect of oral tranexamic acid on massive upper gastrointestinal hemorrhage was evaluated in a randomized double-blind study. Totally 50 patients entered the trial and seven were excluded, leaving 22 placebo treated and 21 tranexamic acid treated for analysis. The groups were comparable regarding sex, age, diagnosis, and initial laboratory data. Transfusions requirements and operation frequency did not differ. Mortality was slightly reduced and death delayed in tranexamic acid treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…Similar results reported by Biggs et alin 197618 were not confirmed either by Engqvist et al"9 or by Bergqvist et al 20 The latter two studies, however, included only patients with all types of massive bleeding, and we consider that antifibrinolytic treatment is less likely to be successful in large arterial or variceal haemorrhages.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results reported by Biggs et alin 197618 were not confirmed either by Engqvist et al"9 or by Bergqvist et al 20 The latter two studies, however, included only patients with all types of massive bleeding, and we consider that antifibrinolytic treatment is less likely to be successful in large arterial or variceal haemorrhages.…”
Section: Discussionsupporting
confidence: 86%
“…Duplicates, nonrandomized studies, trials on patients without upper gastrointestinal bleeding and trials that did not assess tranexamic acid were excluded. Seven randomized trials (described in eight references) on tranexamic acid vs. placebo published as full paper articles fulfilled our inclusion criteria 15, 16, 19–24 . No additional trials were identified in the manual searches or through correspondence with experts.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the included trials used a two‐arm parallel group design 19–24 . In one trial, 15 a three‐arm parallel group design was used and patients were randomized to tranexamic acid, cimetidine or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Seven of the identified trials were also included in a Cochrane systematic review on the effectiveness of TXA in upper gastrointestinal bleeding. 18 The pooled result shows a statistically significant reduction in the risk of death in patients receiving TXA (relative risk 0.66, 0.47 to 0.93) (figure⇓).…”
mentioning
confidence: 99%